2020
DOI: 10.1101/2020.10.26.20215475
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and safety of phentermine/topiramate in adults with overweight or obesity: A meta-analysis and systematic review

Abstract: Objective: To examine the association between phentermine/topiramate therapy and weight loss and adverse events in adults with overweight problems or obesity by meta-analysis and systematic review. Methods: Medical Subject Headings (MeSH) and free-text terms related to phentermine/topiramate were selected to search for eligible trials in PubMed, Cochrane Central Register of Controlled Trials (CENTRAL), and EMBASE up to April 18, 2020. The quality of randomized controlled trials was evaluated by Cochrane risk-o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 17 publications
(43 reference statements)
0
6
0
2
Order By: Relevance
“…Examples include, phentermine, an appetite suppressant, and topiramate, an antiepileptic, which have both been approved to treat obesity by the US Foods and Drug Administration (FDA); 5,6 however, they can have significant neurorelated side effects. 7 Phenylpropanolamine, a metabolic stimulant, has been used to treat obesity in the US; however, it has been shown to increase the risk of haemorrhagic stroke. 8 Orlistat, a nutrition absorption inhibitor, is available worldwide as an obesity treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Examples include, phentermine, an appetite suppressant, and topiramate, an antiepileptic, which have both been approved to treat obesity by the US Foods and Drug Administration (FDA); 5,6 however, they can have significant neurorelated side effects. 7 Phenylpropanolamine, a metabolic stimulant, has been used to treat obesity in the US; however, it has been shown to increase the risk of haemorrhagic stroke. 8 Orlistat, a nutrition absorption inhibitor, is available worldwide as an obesity treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Duas pesquisas avaliaram a combinação do Topiramato com a metformina. Outras cinco avaliaram a combinação do Topiramato com a fentermina [14][15][16][17][18][19][20] ; Efeitos e segurança do uso off label do topiramato na perda de peso conforme mostrou a maioria das pesquisas analisadas, pois apenas em uma das pesquisas foi possível identificar, que a terapia combinada de Topiramato e fentermina não foi bem tolerada, em que mais da metade dos pacientes parou de tomá-lo devido aos efeitos adversos 16 .…”
Section: Resultsunclassified
“…Em uma meta-análise de ensaios clínicos randomizados a terapia com fentermina combinada com o Topiramato resultou em uma perda de peso de 7,73 kg, reduziu a circunferência da cintura, a pressão arterial, os níveis de açú-car no sangue e os níveis de lipídios. Os efeitos adversos associados ao tratamento incluíram principalmente disgeusia, parestesia, boca seca 19 .…”
Section: Resultsunclassified
“…103 A recent misanalysis indicated that the highest dose of this combination, that is, 15 mg of phentermine and 92 mg of topiramate produced an average weight loss of 8.25 kg. 104 Common side effects included dysgeusia, dry mouth, constipation, paresthesias, dizziness, and insomnia. 103,104…”
Section: Phentermine/topiramatementioning
confidence: 99%
“…104 Common side effects included dysgeusia, dry mouth, constipation, paresthesias, dizziness, and insomnia. 103,104…”
Section: Phentermine/topiramatementioning
confidence: 99%